2019
DOI: 10.1075/hcp.65.13zac
|View full text |Cite
|
Sign up to set email alerts
|

The development of the abstract scientific concept of heat energy in a naturalistic classroom setting

Abstract: Science aims to understand the physical and living world around us. To do this, it requires us to develop abstract ways of thinking. The aim of this chapter is to describe and explain how the abstract concepts of heat energy and heat transfer emerge and evolve during two secondary (high) school science lessons, by providing an account of how they are linguistically represented in discourse using a cognitive discursive framework. The analysis of a teacher-led demonstration, a group writing task, and an intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This study is clearly significant and demonstrates how important it is for teachers to understand how metaphors work in their discipline. However, although metaphors play a key role in how scientists do and communicate science (Brown 2003;Reynolds 2018), I have recently shown that it is not the only cognitive process that is involved in the development of abstract thought in a naturalistic setting such as a classroom (Zacharias 2018(Zacharias , 2019. Indeed, as noted by Langacker (2008a), the metaphorical process is just one of several possible cognitive processes that are involved in the creation and use of abstract thought.…”
Section: Abstract Concepts Learning and Languagementioning
confidence: 99%
See 1 more Smart Citation
“…This study is clearly significant and demonstrates how important it is for teachers to understand how metaphors work in their discipline. However, although metaphors play a key role in how scientists do and communicate science (Brown 2003;Reynolds 2018), I have recently shown that it is not the only cognitive process that is involved in the development of abstract thought in a naturalistic setting such as a classroom (Zacharias 2018(Zacharias , 2019. Indeed, as noted by Langacker (2008a), the metaphorical process is just one of several possible cognitive processes that are involved in the creation and use of abstract thought.…”
Section: Abstract Concepts Learning and Languagementioning
confidence: 99%
“…This includes not only Langacker's proposal but also other key cognitive phenomena (e.g. image schemas and epistemic modality) that have been shown to play a significant role in the learning process (Zacharias 2018(Zacharias , 2019. Thus, the analysis in this chapter will focus on the following construal operations: schematization categorization, image-schemas (source-path-goal; container) and Hart's (2011) classification of epistemic modality.…”
Section: A Model Of Linguistic Knowledgementioning
confidence: 99%